2013
DOI: 10.1002/etc.2202
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and effects of 90‐day oral exposure to Dechlorane Plus in quail (Coturnix coturnix)

Abstract: While a number of studies have addressed bioaccumulation of the flame retardant Dechlorane Plus (DP), little information is available regarding the adverse effects of DP on animals, especially on bird species. In the present study, male common quails (Coturnix coturnix) were consecutively exposed to commercial DP-25 by gavage for 90 d at 1-mg/kg/d, 10-mg/kg/d, and 100-mg/kg/d dosages. Concentrations of DP isomers in liver, muscle, and serum were determined after exposure. Liver enzyme activity involved in xeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Li et al (2013a,b) found some evidence on the effect of DP on hepatic enzyme activities in laboratory studies. Hepatic metabolism of DP significantly decreased enzyme activity of 7-pentoxyresorufin-O-demethylase (PROD) and elevated activity of erythromycin N-demethylase (ERND), and the antioxidant enzyme catalase were observed in quail after exposed by DP (Li et al, 2013b). Moreover, rats exhibited increased enzyme activity of CYP 2B2 along with lower mRNA expression levels of sulfotransferase 1A1, 1C2, and 2A1 in the lose dosage-DP group (Li et al, 2013a).…”
Section: Isomer-specific Bioaccumulation Of Dp In Different Tissuesmentioning
confidence: 94%
See 1 more Smart Citation
“…Li et al (2013a,b) found some evidence on the effect of DP on hepatic enzyme activities in laboratory studies. Hepatic metabolism of DP significantly decreased enzyme activity of 7-pentoxyresorufin-O-demethylase (PROD) and elevated activity of erythromycin N-demethylase (ERND), and the antioxidant enzyme catalase were observed in quail after exposed by DP (Li et al, 2013b). Moreover, rats exhibited increased enzyme activity of CYP 2B2 along with lower mRNA expression levels of sulfotransferase 1A1, 1C2, and 2A1 in the lose dosage-DP group (Li et al, 2013a).…”
Section: Isomer-specific Bioaccumulation Of Dp In Different Tissuesmentioning
confidence: 94%
“…Several laboratory exposure experiments also provided evidence for that. No dechlorinated products of DP has been detected in DP exposed juvenile rainbow trout (Tomy et al, 2008), common carp (Zeng et al, 2014) and quail (Li et al, 2013b). Additionally, Zeng et al (2014) reported that the dechlorinated analogs of DP were eliminated more rapidly (20.4% and 14.8% of syn-Cl 11 -DP and anti-Cl 11 -DP) than their corresponding parent chemicals (3.8% and 3.2% of syn-DP and anti-DP) in organisms.…”
Section: Dp Dechlorination Productsmentioning
confidence: 99%
“…In Chinese sturgeon, liver also showed higher dechlorane concentrations than muscle and adipose tissue (Peng et al, 2012). Sequestration of DP isomers by hepatic proteins could be a cause for their disposition in the liver although this was not identified (Li et al, 2013b). Exposure to xenobiotic pollutants such as polychlorinated dibenzo-p-diosins, polychlorinated dibenzo-furans, and coplanar PCBs may induce hepatic binding proteins leading to hepatic sequestration of the compounds (Kubota et al, 2004).…”
Section: Dynamic Tissue Distribution and Isomer Compositionmentioning
confidence: 98%
“…For example, different ratios of anti-DP to total DP (f anti ) of a biota may be due to the accumulation of different DP isomer compositions from the environment (Xian et al, 2011) and perhaps due to isomer-specific bioavailability of DP in the biota. In Previous studies, accumulation of DPs in juvenile rainbow trout (Tomy et al, 2008), rat (Li et al, 2013a), and Quail (Li et al, 2013b) has been investigated in laboratory experiment. Different accumulation potential for anti-and syn-isomer was observed in rainbow trout, rat and quail.…”
Section: Introductionmentioning
confidence: 99%
“…These differentially expressed proteins may induce cell proliferation, apoptosis, and oxidative stress in juvenile Chinese sturgeons (Liang et al, 2014). Oxidative stress in other test organisms such as quail, mice, and earthworms caused by DP exposure was also investigated (Wu et al, 2012;Li et al, 2013;. A recent study by Gagné et al (2017) reported that DP induces oxidative stress in Mytilus edulis (blue mussels.)…”
Section: Neurotoxicitymentioning
confidence: 99%